Impact of HBV therapy on the incidence of hepatocellular carcinoma. (February 2014) - Triolo, Michela; Corte, Cristina Della; Colombo, Massimo
Abstract: Hepatocellular carcinoma (HCC) is a frequent, long term complication of chronic infection with hepatitis B virus (HBV) with an annual incidence ranging from 2 to 5%, often independent from the histological stage of underlying liver disease and serological status. Nevertheless, HCC is more often seen in older patients in whom HBV has been asserting its pro‐oncogenic properties through both indirect and direct mechanisms. In Europe, HBV‐related HCC is associated with cirrhosis in most patients, whereas this is not true in Asia and Africa where the tumour is also common among carriers with mild hepatic fibrosis, probably because of the coexistence of environmental co‐carcinogens (aflatoxin) and long standing infection that is often acquired perinatally. Since hepatitis B‐related carcinogenesis develops independently of the onset of cirrhosis, antiviral treatments such as nucleo(t)side analogues (NAs) that may result in the regression of fibrosis, prevent clinical decompensation and variceal bleeding, often fail to prevent HCC. Studies enrolling patients treated with lamivudine or rescued with adefovir, i.e. regimens characterized by limited potency and a low to moderate genetic barrier, have clearly been shown to help prevent HCC in patients with chronic hepatitis but not in those with cirrhosis, and in general not in patients that cannot achieve a sustained virological response. More potent anti‐HBV drugs, such as entecavir and tenofovir, have been shown to improve the prevention of HCC in responders with cirrhosis, although HCC may still occur even in low risk patients. To attenuate HCC related outcomes, HBV replication must permanently be suppressed and HCC surveillance by abdominal ultrasound should be maintained even in responder patients.